Kajian Kualitastif Peran Taman Baca (TBM) Dalam Meningkatkan Kreativitas Masyarakat Di Kota Padang Panjang - Wilda Afdhilla; Cut Afrina (Jurnal Ilmu Perpustakaan dan Informasi Islam, 2022)
This paper discusses the qualitative study of the role of reading gardens in increasing community creativity in the city of Padang Panjang. The aim is to find out if there is an increase in community creativity with the Rimba Bulan TBM in Padang Panjang City. The research method used is a qualitative method with a phenomenological approach. Data were collected through observation, interviews, and documentation. The results of the study indicate that the existence of the reading garden plays a very important role in the community, the community can develop skills through activities held by TBM Rimba Bulan. From these activities, the community can increase their creativity with curiosity and many people ask questions in participating in the activities held by TBM